Analisis Kinematika Jump Smash pada Olahraga Bolavoli dengan Pendekatan Dua Dimensi Gerak - Widiantari, Ni Luh Gde; Astrawan, I Putu; Widhiyanti, Komang Ayu Tri; Kresnayadi, I Putu Eri; Indrawathi, Ni Luh Putu; Bagia, I Made (MAN Insan Cendekia Jambi, 2025)
This study investigated the influence of the jump smash technique (with and without approach) on the accuracy and kinematic parameters of volleyball players' movements, utilizing two-dimensional video analysis (Kinovea) on 12 club members. The kinematic analysis results showed significant differences in three key variables: jump height, external shoulder rotation, and backward trunk lean, where the jump smash technique with approach demonstrated superior values. Although the accuracy data indicated a higher average for the technique without approach (3.85 vs. 3.02), the study concluded that the jump smash technique with approach provided a more significant overall impact on both accuracy and changes in kinematic parameters in the players.volleyball club, when compared to the jump smash technique without a run-up.